The use of stochastic approaches in computational modeling of professional tasks in the training of future personnel in the field of physical education and sports - Lykova K.G. ,; Shchuchka T.A. ,; Gnezdilova N.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is aimed at developing a methodological justification for solving problems in probability theory using the Python programming language in the process of professional training of students specializing in physical education and sports. Methods and structure of the study.Asanapproachtosolvingprobabilisticproblemsinvolvingindependentrepeatedtrials(inparticular,BernoulliandPoissonformulas),theuse of specializedPythonlibrariessuchasNumPy,SciPy,Matplotlib,Seaborn,Pandas,SymPyandScikit-learn is proposed. The practicalimplementationandtesting of thisapproach was carried out within the framework of the academicdiscipline"Methods of mathematicalinformationprocessing" by studentsstudying in thedirection of 44.03.05Pedagogicaleducation(profile"Physicalculture, Life safety"). Results and conclusions. As a result of the research, a method was developed for solving probabilistic problems related to independent repeated tests (Bernoulli and Poisson formulas) through the use of Python libraries in the context of professional training of specialists in the field of physical education and sports. The integration of the research results into the methodological support of the educational process will expand the available resources for the digital transformation of higher education and contribute to the formation of students' competencies: universal (the ability to solve standard professional tasks based on digital technologies) and professional (the ability to apply mathematical methods in combination with computer tools for creating and analyzing models of varying degrees of abstraction).